Modernizing Finance through Digital Innovation in LIC and PNB Housing Finance - Sesha Sai Sree Jitta (Involvement International Journal of Business, 2025)
Digital transformation has significantly reshaped the financial services sector in India, compelling traditional institutions like the Life Insurance Corporation of India (LIC) and PNB Housing Finance to adopt customer-centric innovations. This study examines how both organizations integrate digital tools and strategies to improve efficiency, customer engagement, and overall performance. The research employed a qualitative descriptive design, analyzing secondary data from reports, company releases, and scholarly studies between 2020 and 2025. Comparative evidence was reviewed to identify technological adoptions, customer outcomes, and operational impacts. Key indicators such as policy growth, loan disbursement rates, and customer service efficiency were highlighted. Findings reveal that LIC achieved notable progress with the ANANDA app, issuing 1.15 million policies by 2024 with 42.84% YoY growth, and enhanced customer service using AI-powered chatbots, reducing complaint resolution times by 30%. The NextGen Digital Platform and Project DIVE further advanced personalization and omnichannel engagement. PNB Housing Finance demonstrated a 27% annual increase in loan approvals through AI-driven underwriting, launched a fully digital loan application system, and redesigned its customer segmentation strategy, resulting in a 68.4% rise in affordable housing disbursements. The findings indicate that while LIC focuses on modernization and institutional resilience, PNB emphasizes rapid lending growth and inclusivity. Both align with broader digital adoption trends in India’s financial sector. However, challenges remain in risk governance, technological dependency, and inclusion of underserved populations.